Laser Vision Correction for Regular Myopia and Supracor Presbyopia: A Comparison Study - Bojan Pajic; Zeljka Cvejic; Horace Massa; Brigitte Pajic-Eggspuehler; Mirko Resan; Harald P. Studer (Applied Sciences, 2020)
A study to compare femto-presbyLASIK to standard myopia femto-LASIK refractive surgical correction with a total of 45 candidates was performed. The goal was to identify a more specific set of indications for presbyopia LASIK treatments. The results showed thoroughly good uncorrected visual acuity for myopia (decimal: 1.01 ± 0.15) as well as for presbyLASIK (decimal: 0.78 ± 0.17) corrections. Astigmatism was comparable in both groups and did not change significantly from preoperative (0.98D ± 0.53 SD) to postoperative (1.01D ± 0.50 SD). Our study results suggest, that presbyLASIK treatment is as safe and effective as regular LASIK myopia correction and can hence be recommended to treat presbyopia.